Suluk pedalangan literature in a semiotic perspective - Sukisno, Sukisno (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
Suluk pedalangan is a form of Javanese literary work, a type of poetry sung by a dalang (puppeteer) in a wayang kulit (shadow puppet) performance. Semiotically, Suluk functions to explain the characterization of scenes whether they are grand, tense, sad, or happy in accordance with the pathet (arrangement of notes) in karawitan (traditional Javanese gamelan music). This research aims to identify and understand the characteristics of suluk from a semiotic perspective. The method used is descriptive qualitative. The data source is Suluk Pedalangan which was collected by Padmosoekotjo (1978). The results of the research show that the suluk pedalangan texts use the Old Javanese language krama alus and krama madya. The results of the research show that the sulukan in wayang kulit performances has the characteristics of being one of the puppetry literature performed (sung) by puppeteers adapted to the pathet and time. When sung by the puppeteer, the sequence of sulukan is adjusted to the time, rhythm (pathet), and kempyung note sequence (beating two notes together with a distance of two notes). Semiotically, the meaning and function of sulukan in setting the atmosphere hold an important position, broadly serving to intensify, embellish, enhance, and shape the atmosphere in various scenes. Textually, sulukan basically refers to the scenes presented. However, if you do not know the meaning of the words, symbols and figures of speech used in sulukan, the aesthetic value and dramatic atmosphere of the scenes presented in wayang kulit performances will be less meaningful. Philosophically, the meaning of sulukan in relation to the sequence of kempyung notes and the time they are expressed symbolizes the journey of a human life, from birth, childhood, adolescence, adulthood, and old age.Keywords: Puppetry literature, semiotics, sulukan, wayang